Low-dose rituximab followed by mycophenolate mofetil for steroid-dependent/frequently relapsing nephrotic syndrome in children: a case series - Song, Jide; Chang, Hong; Lin, Yi; Shan, Chunrong; Liu, Jia; Zhang, Ranran; Nie, Nana; Bai, Cui; Gao, Shan; Zhang, Qiuye; Wang, Dahai (Frontiers in Pharmacology, 2025)
BackgroundRituximab (RTX) has gradually been accepted as a treatment for frequently relapsing nephrotic syndrome (FRNS) or steroid-dependent nephrotic syndrome (SDNS) in children, but no standardized recommendations for the dosage and combination therapy exist. Additionally, the efficacy and safety of low-dose RTX in FRNS/SDNS remain unclear, although it has been used to treat some autoimmune diseases.MethodsWe report a case series of 24 children diagnosed with FRNS/SDNS treated with low-dose RTX followed by mycophenolate mofetil (MMF) for maintenance of remission of nephrotic syndrome between August 2021 and February 2023. These patients were followed up for at least 12 months.ResultsThe mean total dose for the initial four administrations of low-dose RTX was 470.83 ± 62.41 mg, which was significantly lower than the calculated values for one standard dose (525.62 ± 125.62 mg; P = 0.006) and two standard doses (1051.2 ± 251.23 mg; P < 0.001). After treatment initiation, the median follow-up was 24.6 (16.8, 28.5) months. At the 1-year follow-up, no child had experienced treatment failure, and the relapse-free rate was 83.3%. At the last follow-up, two children had experienced treatment failure, with both having frequent relapses, and the relapse-free rate was 75%. Compared with the calculated standard dose of RTX, low-dose RTX followed by MMF was less costly. No serious adverse reactions were observed during RTX use or follow-up, except for one death due to delayed treatment of severe infection.ConclusionLow-dose RTX followed by MMF can extend the remission duration of FRNS/SDNS in children, and decrease the economic burden on families, while offering good safety.